Computer Tomography Features of Antineutrophil Cytoplasm Antibody-associated Vasculitis-interstitial Lung Disease and Its Correlation with Antineutrophil Cytoplasmic Antibody Concentration - Hongmei WANG; Junlin LI; Yuqing DONG; Yueyang ZHANG; Renhuan YAO (CT Lilun yu yingyong yanjiu)
This study systematically analyzed the CT imaging features of patients diagnosed with ANCA-associated vasculitis (AAV)-related interstitial lung disease (ILD) at the time of their first diagnosis. The types and distribution characteristics of the lesions and their correlation with laboratory findings were investigated. A retrospective study was conducted on 92 patients with newly diagnosed AAV-ILD. Clinical and CT imaging data were collected. CT imaging data were analyzed qualitatively and quantitatively to evaluate lesion types (e.g., ground-glass opacities, reticulations, honeycombing, consolidation, and traction bronchiectasis) and their distribution patterns. The severity of the lesions was quantified using a pulmonary fibrosis scoring system, and the correlation between imaging features and laboratory indices was analyzed. AAV-ILD was more commonly observed in elderly male patients. Honeycombing and reticulations were the most common CT-imaging findings, with lesions primarily distributed in the bilateral lower lungs and peripheral regions. AAV-ILD predominantly exhibited a usual interstitial pneumonia (UIP) pattern. A significant positive correlation was also observed between the pulmonary fibrosis score and myeloperoxidase (MPO) concentration and between honeycombing scores and MPO concentration. The CT features of AAV-ILD are unique. The correlation between MPO and pulmonary fibrosis suggests that MPO may serve as a potential biomarker for the progression of pulmonary fibrosis. These findings provide important insights into the imaging characteristics and pathological mechanisms of AAV-ILD.